HIV prevalence among children admitted with severe acute malnutrition and associated factors with mother-to-child HIV transmission at Mulago Hospital, Uganda: A mixed methods study - Musiime, Victor; Rujumba, Joseph; Kakooza, Lawrence; Namisanvu, Henriator; Atuhaire, Loice; Naguti, Erusa; Beinomugisha, Judith; Kiggwe, Andrew; Nkinzi, Sharafat; Segawa, Ivan; Matsiko, Nicholas; Babirekere-Iriso, Esther; et al. (Public Library of Science, 2024)
Despite global efforts to eliminate mother-to-child-transmission of HIV (MTCT), many children continue to become infected. We determined the prevalence of HIV among children with severe acute malnutrition (SAM) and that of their mothers, at admission to Mwanamugimu Nutrition Unit, Mulago Hospital, Uganda. We also assessed child factors associated with HIV-infection, and explored factors leading to HIV-infection among a subset of the mother-child dyads that tested positive. We conducted a cross-sectional evaluation within the REDMOTHIV (Reduce mortality in HIV) clinical trial that investigated strategies to reduce mortality among HIV-infected and HIV-exposed children admitted with SAM at the Nutrition Unit. From June 2021 to December 2022, we consecutively tested children aged 1 month to 5 years with SAM for HIV, and the mothers who were available, using rapid antibody testing upon admission to the unit. HIV-antibody positive children under 18 months of age had a confirmatory HIV-DNA PCR test done. In-depth interviews (IDIs) were conducted with mothers of HIV positive dyads, to explore the individual, relationship, social and structural factors associated with MTCT, until data saturation. Quantitative data was analyzed using descriptive statistics and logistic regression in STATAv14, while a content thematic approach was used to analyze qualitative data. Of 797 children tested, 463(58.1%) were male and 630(79.1%) were [less than or equal to]18months of age; 76 (9.5%) tested positive. Of 709 mothers, median (IQR) age 26 (22, 30) years, 188(26.5%) were HIV positive. Sixty six of the 188 mother-infant pairs with HIV exposure tested positive for HIV, an MTCT rate of 35.1% (66/188). Child age >18 months was marginally associated with HIV-infection (crude OR = 1.87,95% CI: 1.11-3.12, p-value = 0.02; adjusted OR = 1.72, 95% CI: 0.96, 3.09, p-value = 0.068). The IDIs from 16 mothers revealed associated factors with HIV transmission at multiple levels. Individual level factors: inadequate information regarding prevention of MTCT(PMTCT), limited perception of HIV risk, and fear of antiretroviral drugs (ARVs). Relationship level factors: lack of family support and unfaithfulness (infidelity) among sexual partners. Health facility level factors: negative attitude of health workers and missed opportunities for HIV testing. Community level factors: poverty and health service disruptions due to the COVID-19 pandemic. In this era of universal antiretroviral therapy for PMTCT, a 10% HIV prevalence among severely malnourished children is substantially high. To eliminate vertical HIV transmission, more efforts are needed to address challenges mothers living with HIV face intrinsically and within their families, communities and at health facilities.
Keywords: HIV ; Mothers ; HIV infections; Malnutrition; Virus testing; Children; Socio economic aspects of health; Nutrition